2017
DOI: 10.1161/atvbaha.117.309249
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Activation of Hypoxia-Inducible Factor 1α Drives Endothelial Dysfunction at Atheroprone Sites

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
144
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(160 citation statements)
references
References 48 publications
(85 reference statements)
14
144
2
Order By: Relevance
“…Also, HIF-1a expression increased in the aortic arch, which is the part of the aorta most affected by disturbed flow. Disturbed flow can directly induce aortic HIF-1a expression, targeting Snai1 (45,46), the master transcription factor of EndMT, and laminar flow can even protect from TGF-binduced EndMT (14). In line with previous findings (10), we observed more matrix deposition close to the endothelium in atherosclerosis-prone areas with disturbed flow.…”
Section: The In Vivo Atherosclerotic Endmt Phenotype Is Closely Resemsupporting
confidence: 92%
“…Also, HIF-1a expression increased in the aortic arch, which is the part of the aorta most affected by disturbed flow. Disturbed flow can directly induce aortic HIF-1a expression, targeting Snai1 (45,46), the master transcription factor of EndMT, and laminar flow can even protect from TGF-binduced EndMT (14). In line with previous findings (10), we observed more matrix deposition close to the endothelium in atherosclerosis-prone areas with disturbed flow.…”
Section: The In Vivo Atherosclerotic Endmt Phenotype Is Closely Resemsupporting
confidence: 92%
“…4 Importantly, we discovered that HIF-1α was required and sufficient for DF-induced upregulation of glycolysis and downregulation of mitochondrial respiration, which played a key role in EC activation assessed by NF-κB activation and expression of pro-inflammatory cytokines and adhesion molecules. While our conclusions about HIF-1α playing a critical role in EC activation under DF agree with those of Feng et al 1 , there are some differences between the two studies. We found that DF induced NADPH oxidase 4 (NOX4)-dependent generation of reactive oxygen species (ROS), which were required for HIF-1α stabilization and downstream effects on glycolysis and EC activation.…”
Section: To the Editorsupporting
confidence: 86%
“…1 Since atherosclerosis develops near branches or bends of arteries where endothelial cells are exposed to low shear stress, these results suggest that HIF-1α activation in endothelial cells may play a causal role in the pathogenesis of atherosclerosis.…”
Section: To the Editormentioning
confidence: 90%
“…7 The molecular mechanisms downstream from NOX4 were not identified by Wu et al 2 ; however, they speculate that reactive oxygen species (ROS) may stabilize HIF1α by inhibiting the activity of PHD and VHL (von Hippel-Lindau) enzymes. Although we observed that the expression of PHD and VHL was not reduced by disturbed flow, 1 further work is necessary to investigate whether flow alters the activity of these enzymes. It should be noted that effects of flow on PHD, VHL, and Cezanne are not mutually exclusive; it is plausible that disturbed flow promotes HIF1α stability by simultaneously enhancing deubiquitination and reducing ubiquitination.…”
mentioning
confidence: 73%
“…In both studies, unbiased transcriptome-based methods identified enriched expression of HIF1α, and its target genes, in endothelial cells exposed to disturbed flow. 1,2 It was also demonstrated, by both studies, that HIF1α-dependent glycolysis promotes vascular inflammation at atheroprone sites via induction of adhesion molecules and other inflammatory mediators. In contrast to Wu et al, 2 our study revealed that HIF1α additionally induces excessive rates of endothelial cell proliferation 1 -a phenotype that has been previously linked with vascular leakiness and atherogenesis.…”
mentioning
confidence: 92%